Seedling Growth and Biomass Production in Hardwickia binata Roxb. as Affected by Seed Size - Ponnammal, N. R.; Arjunan, M. C.; Antony, K. A. (Indian Forester, 1993)
The study was undertaken to find out the effect of seed size and weight of Hardwickia binata on seed germination and early seedling growth under laboratory conditions. Seed germinations seedling growth and its biomass increased with increase in the seed weight and seed size.